Cloud Computing, IaaS, PaaS, Saa EVALUASI PERFORMA MODEL LAYANAN CLOUD COMPUTING: STUDI KOMPARATIF IAAS, PAAS, DAN SAAS DENGAN PENGUJIAN BEBAN BERTINGKAT - Dian Wahyuningsih; Luqman Affandi; Evy Sophia (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2025)
Cloud computing has become a fundamental paradigm in digital transformation, offering three main service models: Infrastructure as a Service (IaaS), Platform as a Service (PaaS), and Software as a Service (SaaS) [1]. This study examines the comparative performance of these three cloud computing service models through multilevel load testing with five different scenarios (50, 200, 500, 1000, and 2000 concurrent users). Using an experimental methodology with Apache JMeter as a testing tool, this study analyzes critical metrics such as response time, throughput, CPU utilization, memory usage, error rate, and availability [2]. The test results show that PaaS provides superior performance with an average response time of 532.2 ms and a throughput of 2562 req/s, exceeding IaaS (597.0 ms, 2428 req/s) and SaaS (656.0 ms, 2342 req/s). In terms of resource efficiency, PaaS shows optimal CPU utilization (68.2%) and the lowest memory usage (5.16 GB) [3]. Cost-performance ratio analysis reveals that PaaS has the best ratio (0.0041-0.0103), followed by SaaS and IaaS. These findings provide practical guidance for organizations in choosing a cloud computing model that suits their technical and financial needs [4].